Determining factors of knowledge management implementation in knowledge-based organizations - Tasmin, Rosmaini; Yap, L.S. (2010)
Knowledge management (KM) is regarded as a potential management tool in running modern organizations.It contributes significant roles in creating long term internal strength and supporting external competitive advantage.The study seeks to gauge level of KM implementation in Multimedia Super Corridor (MSC) status organizations. MSC certified firms are acknowledged as knowledge-based organizations. This study also examines relationship between demography of respondents with KM influential factors in those organizations.Results of 121 data sets have been collected from 4 MSC-status organizations. Mean score and One Way ANOVA are applied to identify the level of KM practices. This also identifies the relation between the demography and KM factors.It is reported that KM practices in MSC status organizations are at medium level. There are significant differences in KM practices with respect to age of respondents and job designation. It is suggested that sufficient attention should be given to culture, information technology, organization structure and people to achieve success in KM implementation.